Rumah Kutai Perak in watercolor painting / Siti Humaini Said Ahmad @ Syed Ahmad ... [et al.] - Said Ahmad@Syed Ahmad, Siti Humaini; Othman, Muhamad Rozali; Ismail, Issarezal; Syed Abu Bakar, Syed Alwi (Universiti Teknologi MARA, Perak, 2021)
This study is done to write an article related to the art exhibition for "Kami SI + SA" entitled Rumah Kutai Perak and identify the systematic process of artwork making. This artwork's process is based on the theory and practice of Ocvirk, Stinson, Wigg, Bone, Cayton (2009) who stated that an artwork contains three basic parts, namely subject, form and content. Subject refers to a person, a thing or an idea while form refers to elements and principles of design that produce equal unity. On the other hand, content is a message or emotion in work, statement, expression or feeling desired by the artist and read by the observer. As a result of Rumah Kutai Perak artwork, an "Artwork Making Process Flow" has been identified. The process flow begins with identifying the subject and idea, followed by capturing the subject through photography. Photography record involved four important factors, such as viewpoint, light and shadow, focal point, and photo quality. These four factors are important because they will affect the final work. The next process is to paint and draw. The elements such as technique identification, colour value application, medium choice and reference artists served as guides for the researcher throughout the artwork making process. After the work is completed, an artist statement was written to describe the artwork. This artist statement informs the message to be conveyed through the artwork, a brief description of the making process, the sources of ideas, and the elements and principals in the artwork's processing. It is hoped that this work process can be used as a reference for other artists to produce artwork in the same context.